Reconstitution of Norovirus-Specific T-Cell Responses Following Hematopoietic Stem Cell Transplantation in Patients With Inborn Errors of Immunity and Chronic Norovirus Infection - Durkee-Shock, Jessica; Cohen, Ariella; Maghzian, Naseem; Pezzella, Gloria; Jensen-Wachspress, Mariah; Hostal, Anna; Barton, Karenna; Gangler, Krista; Dávila Saldaña, Blachy J; Chaimongkol, Natthawan; Bollard, Catherine M; Sosnovtsev, Stanislav V; et al. (The Journal of infectious diseases, 2025)
Chronic norovirus infection (CNI) causes significant morbidity in immunocompromised patients. No effective prevention or treatment currently exists. Two patients with inborn errors of immunity, X-linked severe combined immunodeficiency (X-SCID) and DOCK8 deficiency, were followed longitudinally for clinical course, immune reconstitution, norovirus-specific T-cell (NST) response, B-cell reconstitution, and norovirus-specific antibody production. Samples were obtained in the peri-hematopoietic stem cell transplant (HSCT) setting before and after CNI clearance. The norovirus strain causing CNI was followed longitudinally for norovirus stool viral loads and sequencing. The noroviruses were identified as GII.4 Sydney[P4 New Orleans] in 1 patient and GII.17[P17] in the other. An exacerbation of diarrhea post-HSCT in the patient with X-SCID was consistent with norovirus infection but not with graft-versus-host disease on pathologic samples. Both patients recovered polyfunctional NSTs in the CD4 and CD8 T-cell compartments that recognized multiple norovirus structural and nonstructural viral antigens. T-cell responses were minimal during active CNI but detectable after resolution. Mapping of NST responses between the patient with DOCK8 deficiency and his matched sibling donor were nearly identical. B-cell reconstitution or new endogenous antibody production for immunoglobulin A or immunoglobulin G was not observed. This report is the first to demonstrate reconstitution of NST immunity after HSCT closely temporally aligned with clearance of CNI, suggesting that cellular immunity is sufficient for norovirus clearance.